Removal of Textile Dye by Bentonite and Organo-Bentonite - ALI DIANATI TILAKI, RAMAZAN (Asian Journal of Chemistry, 2010)
In this study, bentonite was modified by alkyl dimethyl benzyl ammonium chloride (ADBAC) in order to obtain an alternative sorbent for dye removal from textile effluents. Two dyes using in textile industry were examined in this study. Aqueous solutions prepared from disperse blue 56 and pigment blue 60 were used and batch kinetic and isotherm experiments were carried out. Data were evaluated for applicability to the Langmuir and Freundlich isotherm models and the removal capacity of organo-bentonite was compared with that of ordinary bentonite. The adsorption was reached in equilibrium within 6 h of contact time. Adsorption kinetics obeys a Pseudo-second order reaction. Adsorption isotherms were fitted with Langmuir and Freundlich models. Corresponding constants of both models were calculated. Adsorption efficiencies were increased with increasing the sorbents dose. Results indicated that 85 and 78 % removal of disperse blue and pigment blue, respectively by organo-bentonite compared with a removal of 52 and 45 % achieved by ordinary bentonite. Adsorption capacity of bentonite for dye removal can be effectively increased by modification with commercial cationic detergent.